Organic fertilizer / Fatin Hakimah, Nur Fatin Atiqah and Fatin Rosliyana - Hakimah, Fatin; Atiqah, Nur Fatin; Rosliyana, Fatin (Universiti Teknologi MARA, Kedah, 2019)
Our group’s innovation is to create an organic fertilizer that can help farmers and students in growing their plants much faster and healthier. By using organic plants such as grasshopper tree as the base product in creating this fertilizer. The uniqueness of this fertilizer is that it uses 100% percent organic plants. It doesn’t use chemical substance to make this fertilizer. As well as the materials used to make this fertilizer is easy to get and is low price for everyone to get this fertilizer. The ammonia content in this fertilizer is very high compared to the organic fertilizer sold in other stalls. Ammonia content affects the rate of plant growth that causes